RELIGIUSITAS DAN PERSEPSI RISIKO DALAM PENGAMBILAN KEPUTUSAN INVESTASI PADA PERSPEKTIF GENDER - Wiwik Lestari (Journal of Business & Banking, 2013)
Entrepreneur activities bring a great contribution to economy creativities. In this case, Indonesia has the majority of Moslem and some of them run their own business. Islam encourages entrepreneurship. This study attempts to investigate the influence of religiosity and risk perception in investment decision making on gender perspective. There are two independent variables namely religiosity and risk perception, while dependent variable is investment decision making, and gender as moderating variable. This uses questionnaires for collecting the data. With 110 Muslims entrepreneurs Sidoarjo, the collected data are analyzed by Generalized Structured Component Analysis (GeSCA) descriptively. The respondents still have not fully implemented religiosity. Respondents also tend to have high risk perception. The result showed that religiosity and risk perception have no effect on investment decision making. Also, gender did not find as a moderator. It indicates that men and women have the same perception on risk when they made investment decisions.